Identification of ISCA1 as novel immunological and prognostic biomarker for bladder cancer - Zhou, Renlong; Peng, Naixiong; Li, Wei (Frontiers in Immunology, 2022)
Background: Iron-sulfur cluster assembly 1 (ISCA1) has a significant effect on respiratory complexes and energy metabolism. Although there is some evidence that ISCA1 gene expression impacts energy metabolism and consequently has a role in tumorigenesis and cancer metastasis in different types of malignancies, no systematic pan-cancer study of the ISCA1 has been conducted. As a result, we sought to investigate ISCA1's predictive value in 33 cancer types as well as its possible immunological function. Methods: We included the pan-cancer expression profile dataset and clinical data from the public database. Firstly, the single-sample Gene Set Enrichment Analysis (ssGSEA) approach was employed for analyzing the immune link in pan-cancer, while the limma package was utilized for analyzing the differential expression in cancer species. Subsequently, CIBERPORT, MCP-counter, TIMER2, quanTIseq, and xCELL were employed for analyzing bladder cancer (BLCA)’s immune infiltration. Least absolute shrinkage and selection operator (Lasso) were employed for choosing the best gene to develop the immune risk scoring model. Results: ISCA1 gene expression was positively related to four immune signatures (chemokine, immunostimulator, MHC, and receptor) in BLCA. Samples of BLCA were sorted into two groups by the best cut-off of ISCA1 expression degree. The group with a high level of ISCA1 expression had a higher risk, suggesting that the ISCA1 gene was a risk factor in BLCA, and its high expression resulted in a poorer prognosis. Additionally, it was noted that ISCA1 was positively linked with these immune checkpoints. Moreover, there was a considerable positive link between ISCA1 and different immune properties in subgroups with different immune checkpoint inhibiting responses. Finally, an immune risk scoring model was made and it showed a better score in comparison to that of TIDE. Conclusion: ISCA1 can be a prognostic marker for a variety of cancers, particularly BLCA. Its high level of expression has a deleterious impact on the prognosis of BLCA patients. This strongly shows that ISCA1 is a significant prognostic factor for BLCA and that it could be used as a new prognostic detection target and treatment approach.